2017
DOI: 10.24952/ee.v5i1.1175
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Learning Style and Students’ Achievement in Reading Comprehension at Grade Xi Sma N Tambangan

Abstract: Penelitian ini membahas tentang hubungan antara gaya belajar dan pemahaman bacaan siswa. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara gaya belajar dan pemahaman bacaan siswa pada kelas XI SMA N 1 Tambangan. Untuk menganalisis data, penelitian menggunakan t hitung. Berdasarkan hasil penelitian, penelitian menunjukkan penghitungan product moment dengan mendapatkan koefisien korelasi rxy = 0,467. Tingkat korelasi yang signifikan dilakukan dengan mengunci rtabel (rt) pada tingkat signifikan 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…In contrast, the auditory learning style was the least common, with only 2 out of 30 students. This differs from Karmila's (2018) research, which found that students at Darul Ulum Islamic boarding school had a variety of learning styles, including auditory, tactile, kinesthetic, and visual. The predominant learning mode among the majority of pupils was auditory.…”
Section: The Types Of Students' Learning Stylescontrasting
confidence: 93%
See 1 more Smart Citation
“…In contrast, the auditory learning style was the least common, with only 2 out of 30 students. This differs from Karmila's (2018) research, which found that students at Darul Ulum Islamic boarding school had a variety of learning styles, including auditory, tactile, kinesthetic, and visual. The predominant learning mode among the majority of pupils was auditory.…”
Section: The Types Of Students' Learning Stylescontrasting
confidence: 93%
“…The learning styles of students were a significant element in influencing their acquisition of skills, particularly in the area of speaking abilities. Karmila (2018) discovered that learning style refers to an individual's innate preference for acquiring, processing, and retaining new knowledge and abilities. Pujiantini (2020) asserts that learning styles refer to customary methods and patterns of gaining knowledge, abilities, or attitudes through study or experience.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, learning styles chosen by students may affect their performance in language learning process. Learning styles has significant correlation with students' achievement in reading comprehension (Karmila, 2018;Hazriviena, 2023) . Generally, Gunawan (2012) classified learning styles into three types which are visual, auditory and kinesthetic.…”
Section: Factors Influencing Inferential Skill In Readingmentioning
confidence: 99%
“…Meanwhile, learning styles is also admitted to have an influence on students' success in inferential skill test as there are many ways that students can apply to study English based on their learning styles preferences (i.e. visual, auditory, kinaesthetic) aligned with (Karmila, 2018;Hazriviena, 2023). It was found that students who are getting used to learn kinaesthetically looked more anxiety when they had reading test of inferential skill since they prefer to study by being active and more practical.…”
Section: The Factors That Influence Students' Inferential Skill Test ...mentioning
confidence: 99%
“…If the main ideas are combined into a single unit, then the main ideas from a series of paragraphs in one discourse are reflected. If reading carefully feels difficult, then this reading step is minimal to answer the questions formulated in the question step (Harida, 2016). This section can run efficiently if the reader really takes advantage of the list of questions, namely reading with the intention of finding answers to the questions that have been made in the list.…”
Section: Readmentioning
confidence: 99%